2020
DOI: 10.1186/s12931-020-01407-y
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium in chronic obstructive pulmonary disease – a review of clinical development

Abstract: Background: Bronchodilators are the mainstay of pharmacological treatment in chronic obstructive pulmonary disease (COPD), and long-acting muscarinic antagonist (LAMA) monotherapy is recommended as initial treatment for Global Initiative for Chronic Obstructive Lung Disease (GOLD) groups B, C, and D. Main body: Tiotropium bromide was the first LAMA available for COPD in clinical practice and, because of its long duration of action, is administered once daily. Tiotropium was initially available as an inhalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 102 publications
(187 reference statements)
0
9
0
Order By: Relevance
“…22 Finally, in a study of 131 community health service centers in Shanghai, only 21%were equipped with pulmonary function monitors. 23 Early intervention in COPD can effectively delay disease progression, 24 but low awareness of the disease among residents, poor diagnosis recognition and treatment by primary care physicians, and a shortage of primary medical care resources mean that too few cases of COPD are recognized. In addition, the criteria for diagnoses are not standardized in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…22 Finally, in a study of 131 community health service centers in Shanghai, only 21%were equipped with pulmonary function monitors. 23 Early intervention in COPD can effectively delay disease progression, 24 but low awareness of the disease among residents, poor diagnosis recognition and treatment by primary care physicians, and a shortage of primary medical care resources mean that too few cases of COPD are recognized. In addition, the criteria for diagnoses are not standardized in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of previous clinical studies have shown that the bacterial resistance to antibiotics and airway mucus hypersecretion are the main bottlenecks of Western medicine in the treatment of acute and exacerbated COPD. The syndrome investigation with a large sample size has found that 75% of patients belong to the category of the phlegm-heat obstructing lung [ 22 24 ]. The TCM prescription formulated according to the symptoms has revealed the mechanisms from the aspects of reducing drug resistance, lowering airway mucus secretion, and enhancing anti-inflammatory effect, and the synergistic effect of TCM prescription with Western medical treatment has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…An inhalation device is a drug delivery tool of inhaled preparations, which has an important influence on the delivery effectiveness and therapeutic efficacy of the drugs to the lungs. Current inhalation devices include pressurized metered dose inhalers (pMDI), 181 dry powder inhalers (DPI), 182 and soft mist inhalers (SMI) 183,184 (Fig. 12).…”
Section: Opportunities For Lung Therapeutics With Inhaled Mofsmentioning
confidence: 99%